SCIENCE TO REALITY. - Van Zanten, Leonard (JOURNAL OF ADVANCES IN PHYSICS, 2023)
Without knowledge physics is devoid of its means to reality. Without wisdom insight remains hidden. And while eyesight is a grandiose thing it is prone to deception. And sight deception however innocent leads to errors. As then nearly all things can be overcome so can the lack of knowledge and insight.